An unusual case of fulminant leptospiral myocarditis: a case report. Issue 4 (21st October 2019) - Khoo, Chun Yuan; Ng, Choon Ta; Zheng, Shuwei; Teo, Loon Yee
Abstract: Background: Fulminant myocarditis secondary to leptospirosis is rare and associated with poor outcomes. Case summary: We describe a 60-year-old gentleman with fulminant leptospiral myocarditis and profound cardiogenic shock requiring veno-arterial extracorporeal membrane oxygenator (VA-ECMO) support. He was given high-dose pulse steroids early on post-VA-ECMO implantation and achieved full recovery. To our knowledge, this is the first reported case of leptospiral myocarditis with multiorgan dysfunction successfully managed by VA-ECMO and high-dose pulse steroids. Discussion: This case report highlights the potential benefits of steroids in the management of leptospiral myocarditis which requires further validation. Early aggressive supportive management with ECMO should be considered in patients with fulminant leptospiral myocarditis.